The Effect of Intellectual Intelligence on Student Learning Outcomes (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The purpose of this study was to determine the effect of intellectual intelligence on student learning outcomes. The method used is a descriptive quantitative approach and uses the correlation method. This research technique uses a questionnaire distributed to 40 students of the research sample, documentation to obtain data on the average final grade of odd semesters. Questionnaire for the Intellectual Intelligence variable with 29 statement items, while the Student Learning Outcomes variable takes data from the final semester scores. Data analysis used pearson product moment analysis and hypothesis analysis. Based on the analysis, it shows that between the Intellectual Intelligence variable and the Student Learning Outcomes variable shows a strong Pearson correlation value. So it can be concluded that there is an influence of intellectual intelligence on student learning outcomes.